PEMANFAATAN TUMBUHAN OBAT TRADISIONAL OLEH MASYARAKAT SEKITAR HUTAN LINDUNG SENTAJO KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Ridho Affan Mustayyib; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research is aimed to find out the types, parts and the pattern of utilization of medicine plants by communities around Sentajo protected forest in Kuantan Singingi Regency. This research was conducted at Sentajo protected forest area in the village of Koto Sentajo Kuantan Singingi Regency Riau Province. It was started from September to October 2016. The sampling method that was used in this research is Purposive Sampling Method. The result of the research showed that there are 89 types of 34 relatives of medicine plants and 39 benefits of plants that were used by communities in the village of Koto Sentajo. There are 63 types of leaves used as traditional medicine. Leaf is the most widely used as a traditional treatment, while the least part is the skin and tubers. The use of medicine plants can be done in the morning, noon, night and early morning depending on the type of illness. Medicine plants can be processed by boiling.KeyWord: Medicinal Plants, Patterns of the Utilization, Sentajo Protected Forest